Withholding of Life-Sustaining Treatment and Mortality in ICU Patients with Severe Acute COPD Exacerbations: A Retrospective French Cohort - Puechoultres P; Jamme M; Abi-Abdallah G; Diop S; Legriel S; Ferré A (International Journal of COPD)
Pauline Puechoultres,1 Matthieu Jamme,2,3 Georges Abi-Abdallah,4 Sylvain Diop,5 Stéphane Legriel,1,6 Alexis Ferré1 1Intensive Care Unit, Versailles Hospital, Le Chesnay, France; 2Intensive Care Unit, West Parisian Private Hospital, Ramsay-Générale de Santé, Trappes, France; 3Department for Research, Studies, Assessment and Statistics (DREES), French Ministry of Health, Paris, France; 4Department of Anesthesiology and Critical Care, APHP, Hôpital Européen Georges Pompidou, Paris, France; Université de Paris, INSERM, IThEM, Paris, France; 5Department of Anesthesiology and Intensive care, Marie Lannelongue Hospital, Le Plessis Robinson, France; 6University Paris-Saclay, UVSQ, INSERM, CESP, Villejuif, FranceCorrespondence: Alexis Ferré, Intensive Care Unit, Versailles Hospital, 177 Rue de Versailles, Le Chesnay, 78150, France, Email aferre@ght78sud.frBackground: Data on withholding life-support (WLS) decisions during acute exacerbations of chronic obstructive pulmonary disease (COPD) in the intensive care unit (ICU) are scarce. This study aimed to identify factors associated with these decisions and their impact on mortality.Methods: We conducted a monocentric retrospective cohort study on all patients admitted to our ICU between 2015 and 2021 for a severe acute exacerbation of COPD. Logistic multivariable regression analysis was performed.Results: We included 463 patients of whom 128 (27.6%) had a decision of withholding of care. The 3-months mortality was 49.2% and 4.8% in the WLS group and in the no WLS group, respectively. Forty-eight patients (10.4%) had advanced healthcare directives. In multivariable analysis, factors associated with a decision of WLS were higher age (odds ratio [+10 years] = 1.93, p < 0.001), immunodeficiency (OR = 3.07, p < 0.001), higher Performance Status (PS) score (OR [+1 point] = 2.10, p < 0.001), long-term oxygen therapy (OR = 4.11, p < 0.001) and shock after ICU admission (OR = 2.43, p = 0.01). In multivariate analysis, factors significantly associated with 3-month mortality included decision of WLS during ICU (OR = 22.98, p < 0.001) and invasive mechanical ventilation (OR = 2.72, p < 0.001).Conclusion: Approximately 30% of COPD patients underwent a decision to withhold life-sustaining treatment. Higher age, immunosuppression, increased PS score, and long-term oxygen therapy were significantly associated with this decision. Nearly half of the patients died within three months following a withholding of care decision.Keywords: COPD, exacerbation, mortality, withholding, life-support